CONSCIENTIOUSNESS AND EMOTIONAL STABILITY ON STUDENTS’ SPEAKING ABILITY THROUGH FLIPPED CLASSROOM - Reflianto Reflianto (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
The purpose of this study was to analyze the differences of students’ speaking ability in the Flipped Classroom model by using 1) audiovisual media, 2) printed media, 3) online learning WhatsApp and Massive Open Online English Course (MOOEC) in terms of students’ personality of conscientiousness and emotional stability. An experimental research method was used in this study where the data taken from 56 students who enroll class eleventh at Senior High School of MAN 3 Padang. They were divided into four different treatment groups. Students’ speaking ability data were collected by using Oral English Competence Test, while the personality data was measured by using questionnaires with 5-point Likert scale. The data analysis used one ways Anacova. Research findings reported that simultaneously the Flipped Classroom Model by using four different media have significant influence on students' speaking ability in terms of their conscientiousness and emotional stability, but partially was not significant differences on students' speaking ability where the conscientiousness have significant effect on students' speaking ability, but not to emotional stability. Flipped Classroom Model by using online learning WhatsApp and MOOEC highly contribute to the improvement of students' speaking ability than printed media. English teachers can take advantages of the use online learning media WhatsApp and MOOEC in the teaching of English speaking.